Exposição e atitudes frente à mídia LGBTQ+: desenvolvimento de medidas e o papel moderador da orientação sexual - Dias, Ericarla Verônica Almeida (2023)
Exposure to positive LGBTQ+ media significantly influences attitude change towards the community, on the other hand, exposure to negative media can increase LGBTphobia. Given this, this work aimed to create and validate the Scales of Attitudes towards LGBTQ+ and Exposure to LGBTQ+ Media, as well as to understand how these are associated with LGBTphobia and personal variables. Three studies were carried out: a systematic literature review, a development and validation study of the two instruments, and a last correlational one. In the end, the results of Study 1 indicate that there are changes in attitudes towards the LGBTQ+ public from exposure to LGBTQ+ media. Study 2 gathered psychometric evidence of the measures developed in the study, presenting the following results: Study 2.1 pointed to a two-factor organization of the Negative Media Exposure Scale (Media with Negative Portraits, α = 0.82 and Media with Positive Portraits , α = 0.80) and a single-factor organization of the LGBTQ+ Media Attitudes Scale (α = 0.91 ). Study 2.2 corroborated these factorial structures, presenting satisfactory fit indices (Mean Exposure: CFI = 0.97, TLI = 0.97, GFI = 0.97, SRMR = 0.07, RMSEA = 0.07 | 90% CI 0.06 - 0.09 | Attitudes: CFI = 1.00, TLI = 1.02, GFI = 0.99, SRMR = 0.01, RMSEA = 0.01 | 90% CI 0.01 - 0.02 ), the discrimination indices of the Exposure scale ranged from 0.54 (Item 5) to 2.11 (Item 6) and those of the Attitudes scale ranged from 1.98 to 5.22, considered very high. Finally, Study 3 found a correlation between negative media representation and attitudes (r = 0.34, p < 0.01), moderated by sexual orientation [b = 0.62, (95% CI = 0.27 - 0.97), t = 3.52, p < 0.01]. Through the scales, we can observe that there is still a predominance of media representation focused on negative aspects, such as victimization and discrimination.